RisK Factors Neonatal Jaundice - Literature Review - Gitta Arinda Faustina (NHM PRESS, 2021)
Jaundice adds 9% causes of infant mortality in Indonesia. Jaundice refers to the yellow coloration of the skin and sclera of the newborns that results from the accumulation of bilirubin in the skin and mucous membranes. This is associated with increased circulating bilirubin levels, a condition known as neonatal jaundice. Related risk factors in mothers and infants should be considered because jaundice may lead to complications, named kernicterus. This secondary study used literature review studies with published articles between 2015 and 2020. Search term of this articles used Boolean operator with the keywords